The nature of engaged teaching in New Zealand secondary schools : a thesis presented in partial fulfilment of the requirements for the degree of Master of Educational Psychology at Massey University, Albany, New Zealand - Patterson, Camille (Massey University, 2014)
The nature of engaged teaching in New Zealand, was examined by interviewing a selection of secondary school teachers working in New Zealand schools. Teachers’ perceptions about how they integrated social, emotional and academic learning into their practice to underpin engaged teaching and promote student wellbeing were explored. Fifteen teachers from suburban secondary schools were interviewed individually to investigate strategies for engaged teaching according to the foundations of the Engaged Teaching model (Weaver & Wilding, 2013). Statements collected from the interviews were recorded and organised around the four foundations of engaged teaching. The teachers prioritised interpersonal relationships and community, in addition to fostering connection, meaning and purpose. These teachers acknowledged cultural contexts to some extent, although this was an area for further development. In general, while many of the teachers emphasised the importance of integrating social, emotional and academic learning in engaged teaching, this terminology was unfamiliar for many of the teachers. It was concluded that overall, the foundations of engaged teaching according to the Weaver and Wilding model (2013) were useful in assisting the teachers to integrate social and emotional learning to promote student wellbeing, and this model was adapted for use in the New Zealand secondary context. Keywords: Social and emotional learning, engaged teaching, student wellbeing, secondary school
Keywords: High school teaching; Effective teaching; Teacher-student relationships; New Zealand; Engaged teaching; Social and emotional learning; Student wellbeing; Secondary school